A blended learning model for creative thinking development - Nuttapong Prasertsung; Alisa Songsriwittaya (Institute of Advanced Engineering and Science, 2026)
Creative thinking is a critical competency in higher education in the industry 5.0 era. Although blended learning (BL) and design thinking (DT) are widely adopted, existing instructional approaches often lack explicit mechanisms for process-level quality regulation across the creative process, leading to inconsistent and insufficiently structured outcomes. To address this gap, this study develops and validates the blended learning design thinking plan-do-check-act (BLDTPDCA) learning model, which embeds the plan-do-check-act (PDCA) cycle as a stage-based quality regulation mechanism within the DT process, rather than as a separate tool. The model incorporates a task–modality alignment linking face-to-face learning with the empathize, define, and ideate stages, and online learning with the prototype and testing stages to support continuous feedback. The study employed a model development and validation design. Five experts evaluated the model using a 19-item index of item-objective congruence (IOC), indicating high content validity (IOC=0.95). The findings demonstrate that the model enables systematic, process-level quality regulation within creative learning activities. This study contributes to the literature by reconceptualizing PDCA as an embedded regulatory mechanism within DT and by providing a structured, theory-informed framework for aligning instructional processes with measurable creative thinking development in higher education.